2021
DOI: 10.1111/jfpp.15741
|View full text |Cite
|
Sign up to set email alerts
|

Zein–resin composite nanoparticles with coencapsulated carvacrol

Abstract: This paper evaluated the potential of zein–resins nanoparticles to act as a carrier for water‐insoluble oil carvacrol. The rosin and shellac were used as natural resins in different mass ratios to plant protein zein. Rosin is one of the natural gums. Shellac is a resinous secretion of the insect. The influence of nanoparticle composition on colloidal properties, encapsulation efficiency, and release of oil was studied. Zeta potential and size of thus prepared nanoparticles were studied. Carvacrol encapsulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…SL-chitosan nanoparticles loaded with bovine serum albumin were reported to have a diameter of 104–280 nm after ionic cross-linking . Anti-solvent precipitation, by dispersing an aqueous ethanol solution with dissolved zein, SL, and carvacrol in water, resulted in nanocapsules with a diameter of 60–150 nm . Another anti-solvent precipitation method that dissolved curcumin and SL in a ternary organic solvent mixture of dimethylformamide, dimethyl sulfoxide (DMSO), and ethanol, followed by sequential mixing with phosphate buffer, resulted in nanocapsules with a diameter of 40 nm .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SL-chitosan nanoparticles loaded with bovine serum albumin were reported to have a diameter of 104–280 nm after ionic cross-linking . Anti-solvent precipitation, by dispersing an aqueous ethanol solution with dissolved zein, SL, and carvacrol in water, resulted in nanocapsules with a diameter of 60–150 nm . Another anti-solvent precipitation method that dissolved curcumin and SL in a ternary organic solvent mixture of dimethylformamide, dimethyl sulfoxide (DMSO), and ethanol, followed by sequential mixing with phosphate buffer, resulted in nanocapsules with a diameter of 40 nm .…”
Section: Introductionmentioning
confidence: 99%
“…13 Anti-solvent precipitation, by dispersing an aqueous ethanol solution with dissolved zein, SL, and carvacrol in water, resulted in nanocapsules with a diameter of 60−150 nm. 14 Another anti-solvent precipitation method that dissolved curcumin and SL in a ternary organic solvent mixture of dimethylformamide, dimethyl sulfoxide (DMSO), and ethanol, followed by sequential mixing with phosphate buffer, resulted in nanocapsules with a diameter of 40 nm. 15 Although a high loading capacity (LC) of 49.3% and a high encapsulation efficiency (EE) of 98.6% were achieved, 15 the encapsulation process is tedious and the use of these organic solvents is a concern for food applications.…”
Section: Introductionmentioning
confidence: 99%
“…fabricated dispersible composite nanoparticles using zein and shellac through an antisolvent coprecipitation method, which differs from the traditional antisolvent precipitation method. Later studies demonstrated that the zein-shellac composite nanoparticles can be used to load carvacrol to obtain the desired release effect. , As shown in Figure C, this method was then used to design ideal colloidal surfactants, such as polylactide (PLA)/shellac dimer particles with one PLA bulb and one shellac bulb for pH-responsive Pickering emulsions . An oat protein-shellac nanoparticle (90–300 nm) delivery system, developed through emulsion followed by cold gelation, could protect the activity of resveratrol in gastric fluid and allowed its controlled release into the small intestine to improve bioavailability .…”
Section: Shellac-based Delivery Systemsmentioning
confidence: 99%